Corrosion Behavior of Lightweight MgO in High Basicity Tundish Slag. Issue 8 (5th May 2021) - Tan, Chong; Liu, Yu; Li, Guangqiang; Yuan, Cheng; Tian, Yufeng; Zou, Yongshun; Huang, Ao
Abstract : Demand for energy saving in steelmaking process, lightweight refractories have attracted great attentions for the excellent thermal insulation. Herein, the corrosion behavior of the lightweight magnesia in the high basicity tundish slag is explored, and compared with that of fused magnesia. The results show that the impurities in the fused magnesia cause more dissolution of magnesia into slag after 60 min. Different from fused magnesia, the penetration layer is found in the lightweight magnesia, where the intercrystalline CaZrO3 –ZrO2 phases are dissolved by the slag. The micropores in the lightweight magnesia provide passages for slag infiltration, but also accelerate the supersaturation of slag in refractory and impede the mass transfer. Furthermore, the residual CaZrO3 –ZrO2 phases in transition layer hinder the further slag infiltration. After 60 min holding, the MgO content in molten slag contacted with lightweight magnesia is lower, implying that the lightweight magnesia is the promising refractory for tundish lining. Abstract : The micropores in the lightweight magnesia provide the passages for slag infiltration, but also accelerate the supersaturation of slag and impede the mass transfer. Furthermore, the CaZrO3 –ZrO2 phases exist in transition layer and hinder the further slag infiltration. Meanwhile, the lightweight magnesia possesses excellent thermal insulation, implying that it is promising for tundish lining.